The Career Development of Peer Counsellors in a Vocational Counselling Program - MacCulloch, Wayne; Cochran, Larry D. (Canadian Journal of Counselling and Psychotherapy, 2011)
Ten secondary students who served as peer vocational counsellors were compared with a matched control group on career development. It was found that peer counsellors improved significantly more than controls on the Career Development Inventory (Super, Forrest, Jordaan, Lindeman, Myers, & Thompson, 1979).